Advances in Human Factors in Simulation and Modeling Proceedings of the AHFE 2018 International Conferences on Human Factors and Simulation and Digital Human Modeling and Applied Optimization, Held on July 21-25, 2018, in Loews Sapphire Falls Resort at Universal Studios, Orlando, Florida, USA - Cassenti, Daniel N. (Advances in Intelligent Systems and Computing, 2019)
This book focuses on computational modeling and simulation research that advances the current state-of-the-art regarding human factors in this area. It reports on cutting-edge simulators such as virtual and augmented reality, on multisensory environments, and on modeling and simulation methods used in various applications, including surgery, military operations, occupational safety, sports training, education, transportation and robotics. Based on the AHFE 2018 International Conference on Human Factors in Simulation and Modeling, held on July 21-25, 2018, in Orlando, Florida, USA, the book serves as a timely reference guide for researchers and practitioners developing new modeling and simulation tools for analyzing or improving human performance. It also offers a unique resource for modelers seeking insights into human factors research and more feasible and reliable computational tools to foster advances in this exciting research field.